HUBUNGAN KINERJA GURU DENGAN MUTU PENDIDIKAN DI SEKOLAH - Agus Fahmi; Hardiansyah Hardiansyah; I Made Angga Suryanata (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2017)
Teacher performance is an important factor in improving the quality of education,especially improving the quality and the quality of education in school can be felt by peopleranging from inputs ( input ), the educational process was going on, until the output (outputproduct) of an educational process. Performance good teacher can be seen from a high workcommitment, and always able to carry out their duties well and has a high dedication . In theeffective performance of teachers and oriented to the quality of education requires acommitment earnestly in quality improvement. the objectives to be achieved in this study areto Know the Teacher Performance Relationship With the quality of education in SMP Negeri3 Central Praya academic year 2015/2016. Total population in this study were 11 teachers.Data collection methods used in this study is documentation method and questionnaire as theprincipal method while the method of interview as a complementary method . While themethod of data analysis using statistical analysis Product Moment Correlation formula. Basedon the calculation formula Product Moment Correlation r hitung results obtained at 0.645 withr tabel value of 0.602 at a significance level of 5 % and N = 11, or ( 0.645 > 0.602 ) . Thisshows that ( Ho ) is rejected and ( Ha ) is accepted . The conclusion of this research is There arelationship Teacher Performance With Quality of Education in SMP Negeri 3 Central Prayaacademic year 2015/2016.